RELEVANSI DAN SIGNIFIKANSI SEJARAH SERTA PERBANDINGAN PENDIDIKAN MULTIKULTURAL DALAM PERSEPEKTIF ISLAM - Aprianti, Nefi; Amin, Alfauzan; Zubaedi, Zubaedi; Ismail, Ismail; Sapruni, Sapruni (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
The uniqueness of these diverse cultures has implications for the mindset, behavior and personal character of each as a tradition that lives in the community and region. Intercultural pluralism provides opportunities for conflict when there is no mutual understanding and respect for each other. This article discusses the relevance and historical significance as well as the comparison of multicultural education in an Islamic perspective as a process to minimize conflict in the context of empowering a plural and heterogeneous society to understand and respect each other and form a character that is open to differences both for Indonesia and views on other countries. One of the efforts that can be made to fight for multiculturalism is through multicultural education. A global perspective on multicultural education that is becoming more useful in promoting core human values. Multicultural education will not only reap the benefits of pluralism, but also become a pillar of academic excellence, a democratic model of pluralistic societies and an attraction for international economies and human resources as they better human relations within their own nations and with other countries in the world that are increasingly interdependent, resulting in religious harmony, nation and state.